2018
DOI: 10.1029/2018wr022908
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatological Drivers of Extreme Floods on Lake Ontario

Abstract: This study examines the hydrologic and climatic conditions that precede major flood events on Lake Ontario, with the purpose of understanding the potential for seasonal forecasts to inform lake level management. Seven late spring/early summer flood events are identified since 1949, including the record‐breaking flood of 2017. The surface climate, atmospheric circulation, and antecedent lake levels for the preceding winter and spring seasons are examined. Results suggest that flood events are caused by differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…This coincides with the timing needed to prepare for and potentially reduce flood risk. While ENSO forecasts can be noisy over the Great Lakes, recent work suggests that nonlinearity in the underlying teleconnections could be used to improve forecast skill (Carter and Steinschneider 2018; Fu and Steinschneider 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This coincides with the timing needed to prepare for and potentially reduce flood risk. While ENSO forecasts can be noisy over the Great Lakes, recent work suggests that nonlinearity in the underlying teleconnections could be used to improve forecast skill (Carter and Steinschneider 2018; Fu and Steinschneider 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Li et al (2012) demonstrated that variations in the western ridge of the North Atlantic subtropical high (NASH) control regional low-level moisture transport over the eastern United States, such that a southwest (northwest) shift in the western ridge position leads to wet (dry) conditions over much of the region. Building from these results, Carter and Steinschneider (2018) recently showed that west-east variations in the position of the NASH are related to late spring and early summer rainfall anomalies over the northeastern United States and Canada that can contribute to flooding in the Great Lakes.…”
Section: Introductionmentioning
confidence: 88%
“…A major flood impacted the shoreline of Lake Ontario in the late spring and summer of 2017, driven primarily by an extended period of high static water levels. Flood levels, defined by static levels above 75.5 m, were reached in late April, and by late May, water levels peaked at 75.88 m, the highest in the 100‐year record (Carter and Steinschneider ). Levels remained elevated for several months afterward, causing widespread property damage linked to inundation and erosion.…”
Section: Introductionmentioning
confidence: 99%